Paying Attention to Technology Innovations : Experimental Evidence from Renewable Energy Markets in Africa - Coville, Aidan; Orozco, Victor; Reichert, Arndt (World Bank, Washington, DC, 2020)
This paper presents results from a randomized field experiment that examined the effects of mass media campaigns informing about a new technology on the adoption decisions of households in rural Senegal. While some communities were exposed to a campaign broadcasted on national radio that informed households about the general benefits and quality of solar lamps, other communities were exposed to the same radio campaign complemented with information that singled out the most suitable lamp type for all main technological applications. The authors exploit the difference between the two campaigns to examine the extent to which certain information characteristics matter for the uptake of the technological innovation. Results from our experiment show that information on optimal lamp types was required to increase adoption of solar lamps on the extensive margin (more people investing in lamps). However, the type-unspecific information increased adoption on the intensive margin (existing users investing in more lamps). These findings can be explained by a simple learning model of selective attention that the authors adjusted to the study setting, where households engage in home production and spend time as well as mental energy to learn about technological features that maximize returns.